The class III PI(3)K Vps34 promotes autophagy and endocytosis but not TOR signaling in Drosophila. - Juhász, G.; Hill, J.H.; Yan, Y.; Sass, M.; Baehrecke, E.H.; Backer, J.M.; Neufeld, T.P. (Journal of Cell Biology, 2008)
Degradation of cytoplasmic components by autophagy requires the class III phosphatidylinositol 3 (PI(3))-kinase Vps34, but the mechanisms by which this kinase and its lipid product PI(3) phosphate (PI(3)P) promote autophagy are unclear. In mammalian cells, Vps34, with the proautophagic tumor suppressors Beclin1/Atg6, Bif-1, and UVRAG, forms a multiprotein complex that initiates autophagosome formation. Distinct Vps34 complexes also regulate endocytic processes that are critical for late-stage autophagosome-lysosome fusion. In contrast, Vps34 may also transduce activating nutrient signals to mammalian target of rapamycin (TOR), a negative regulator of autophagy. To determine potential in vivo functions of Vps34, we generated mutations in the single Drosophila melanogaster Vps34 orthologue, causing cell-autonomous disruption of autophagosome/autolysosome formation in larval fat body cells. Endocytosis is also disrupted in Vps34(-/-) animals, but we demonstrate that this does not account for their autophagy defect. Unexpectedly, TOR signaling is unaffected in Vps34 mutants, indicating that Vps34 does not act upstream of TOR in this system. Instead, we show that TOR/Atg1 signaling regulates the starvation-induced recruitment of PI(3)P to nascent autophagosomes. Our results suggest that Vps34 is regulated by TOR-dependent nutrient signals directly at sites of autophagosome formation.